Time arrival in series forecasting model for tourist National Park Kuala Tahan, Pahang - Megat Muhammad Afif, Megat Muainuddin (2021)
Tourism forecasting can lead to an important element in tourism industry to ensure that each investment by individuals, companies and government is profitable. From economy perspective, eco-tourism is a growing business and it is an important indicator to the tourism industry. It also generates income revenue to the owner and surrounding communities. This research aims to forecast the eco-tourism demand based on number of tourist arrival for both local and foreign tourist at National Park Kuala Tahan, Pahang. The forecasting models used are seasonal autoregressive integrated moving average (SARIMA) and exponential smoothing. Both forecasting models are compared and assessed using Mean absolute percentage error (MAPE), root mean square error (RMSE) and mean absolute error (MAE). The result demonstrated that the best model to forecast the number of tourist arrival in National Park Kuala Tahan, Pahang is SARIMA (1,0,0)(1,0,1) 12 which is based on the smallest value of MAPE, RMSE and MSE. Hence, the exponential smoothing is not as good as the SARIMA model in forecasting tourist arrival for the data used. In future study, SARIMA model can be used to compare between the local and foreign tourist arrival for eco-tourism destination.